Biomass requirements from natural pastures for livestock grazing and soil protection in the eastern African highlands - Mwendera, E.J.; Mohamed-Saleem, M.A.; Tadesse, A. (1999)
The problem of seasonal shortages of herbage production from natural pastures in the Ethiopian highlands was investigated. This was done by comparing the available biomass amounts on the pastures with biomass amounts required for livestock grazing and for protecting land slope from soil erosion within a given slope limit at different times of the year. It was observed that the pattern of biomass availability and the requirements for livestock grazing and soil protection vary seasonally, as grazing is concentrated in, different parts of the watershed at different times. It was further observed that from March to September feed supplementation is necessary since the available biomass quantities from natural pastures and crop residues on slopes above 3% are generally inadequate to meet livestock and soil protection requirements. However, with changes in the grazing management to regulate grazing pressure, herbage production on these slopes may be increased to adequately meet livestock needs while protecting the soil from erosion. Herbage production could further be improved through fertilizer application, provision of feed supplements during times of shortfall in biomass, and/or by leaving animal dung on the pasturelands instead of collecting it for fuel and other uses. The cost of feed supplements relative to the cost of restoring degraded land as a result of allowing grazing to exceed the safe limits should be investigated.